Sexuality in old age: taboos and reality - Rozendo, Adriano da Silva (2015)
Stereotypes of an asexual old age remain in the social imaginary. This work is based on quantitative and qualitative data of a research focused to analyze the way sexuality have been portrayed and experienced in old age. 32 seniors aged between 60 and 75 years were interviewed. Topics as homoaffectivity and casual sex still untouchable in old age. Even being a taboo, sexuality still being experienced by most of the elderlies.